The Electroretinogram as a Potential Biomarker of Psychosis in Children at Familial Risk. Issue 1 (5th February 2022) - Moreau, Isabel; Hébert, Marc; Maziade, Michel; Painchaud, Alexandra; Mérette, Chantal
Abstract: We previously proposed the electroretinogram (ERG) as a promising biomarker of major psychiatric disorders such as schizophrenia (SZ) and bipolar disorder (BP), given that we found anomalies in the ERG parameters of patients with these diagnoses as well as in their children who are at high risk (HR) of developing such disorders. The aim of the present study is to investigate the usefulness of the ERG for individual detection, among HR children, of an ERG profile resembling that of a SZ patient, as this may indicate a stronger likelihood of transition to psychosis. Using a logistic regression model previously derived from the ERG assessments of SZ patients and control (CT) subjects, individual risk scores were obtained for 61 HR and 80 CT youth. Those with a very high individual risk score were classified as "schizophrenia-like" ( SZ-like ). We found that the HR subjects were 3.5 times more likely to be classified as SZ-like than the CT subjects (95% CI [1.1–11.8]). Furthermore, among the HR subjects, we studied the relationship between the SZ-like classification and psychotic-like experiences and found that HR subjects classified as SZ-like were 2.7 times more likely than all remaining HR subjects to have experienced psychotic-like symptoms (95% CI [1.3–4.6]), and 6.8 times more likely than those with a very low individual risk score (95% CI [1.4–40.4]). Our results suggest that a model previously derived from ERG data on SZ patients could be a potential tool for early detection of the susceptibility to a psychotic-like disorder among familial HR children.